1997
DOI: 10.1083/jcb.137.6.1421
|View full text |Cite
|
Sign up to set email alerts
|

The Small GTPases Rho and Rac Are Required for the Establishment of Cadherin-dependent Cell–Cell Contacts

Abstract: Cadherins are calcium-dependent cell–cell adhesion molecules that require the interaction of the cytoplasmic tail with the actin cytoskeleton for adhesive activity. Because of the functional relationship between cadherin receptors and actin filament organization, we investigated whether members of the Rho family of small GTPases are necessary for cadherin adhesion. In fibroblasts, the Rho family members Rho and Rac regulate actin polymerization to produce stress fibers and lamellipodia, respectively. In epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
611
9
9

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 716 publications
(657 citation statements)
references
References 76 publications
28
611
9
9
Order By: Relevance
“…p120 ctn also alters the relative activities of the small G-proteins Rho A, Rac, and Cdc42 Grosheva et al, 2000;Noren et al, 2000). This may well be related to changes in the activities of these proteins initiated by adhesion Noren et al, 2001) and involved in actin-driven cadherin clustering (Braga et al, 1997(Braga et al, , 1999Jou and Nelson, 1998;Takaishi et al, 1997).…”
Section: The Plot Regulatory Interactions At the Cytoplasmic Domain Omentioning
confidence: 99%
“…p120 ctn also alters the relative activities of the small G-proteins Rho A, Rac, and Cdc42 Grosheva et al, 2000;Noren et al, 2000). This may well be related to changes in the activities of these proteins initiated by adhesion Noren et al, 2001) and involved in actin-driven cadherin clustering (Braga et al, 1997(Braga et al, , 1999Jou and Nelson, 1998;Takaishi et al, 1997).…”
Section: The Plot Regulatory Interactions At the Cytoplasmic Domain Omentioning
confidence: 99%
“…Recent studies have revealed that the cadherin-based cell-cell adhesions are regulated by Rac1 small GTPbinding protein (Rac1) (Braga et al, 1997;Takaishi et al, 1997). We checked the localization of mlin-7 in MDCK cell lines stably expressing a dominant active (V12Rac1) or negative (N17Rac1) mutant of Rac1.…”
Section: Tissue Distribution Of Rat Lin-7mentioning
confidence: 99%
“…Rac regulates formation of lamellipodia and membrane ru ing in various types of cultured cells (for reviews, see Hall, 1994Hall, , 1998. Rac regulates actin assembly at the adherens junction of the wing disc epithelium in Drosophila (Luo et al, 1994;Eaton et al, 1995), the formation of cadherin-dependent cell-cell adhesion in MDCK cells and human keratinocytes (Braga et al, 1997;Hordijk et al, 1997;Takaishi et al, 1997;, and tight junction in MDCK cells . Cdc42 regulates the formation of ®lopodia in various types of cells (for review, see Hall, 1998).…”
Section: Introductionmentioning
confidence: 99%